Antimicrobial compound from Trichoderma harzianum, an endophytic fungus associated with ginger (Zingiber officinale) - Harwoko Harwoko; Jungho Lee; Georgios Daletos; Michael Feldbrügge; Rainer Kalscheuer; Peter Proksch (Faculty of Medicine, Universitas Islam Indonesia, 2021)
Background: Genus Trichoderma of fungal kingdom are largely used as biological control agents due to broad-spectrum activity against plant pathogens.Objective: This study aimed to investigate Trichoderma harzianum, an endophytic fungus obtained from ginger (Zingiber officinale) leaves.Methods: The chemical structures of the isolated compounds were deduced on the basis of UV, 1H NMR and MS data analyses, as well as comparison with literature.Results: Two known tetramic acid derivatives were isolated from this fungus, including harzianic acid (A) and isoharzianic acid (B). Compound B inhibited the growth of a corn pathogenic fungus, Ustilago maydis, with inhibition zone diameter (39 ± 0.33 mm) larger than nystatin (29 mm). Additionally, iso-HA (B) revealed antibacterial effect towards Staphylococcus aureus with MIC value of 25 µM. However, both compounds showed no cytotoxicity against human cervical and ovarian cancer cell lines.Conclusion: T. harzianum produced antimicrobial compound like iso-HA which has potential application either in agricultural or health.